Role of arthroscopy for early diagnosis and early therapeutic intervention in knee synovitis compared to histopathology - Gandra, Arvind (International Journal of Research in Orthopaedics, 2018)
Background: Arthroscopy has been found to be very useful for early diagnosis and also found useful for early therapeutic interventions in patients with synovitis of the knee joint disorders. The objective of the study was to study the role of arthroscopy for early diagnosis and early therapeutic intervention in knee synovitis. Methods: Hospital based prospective study was carried out at Department of Orthopedics, Dr. D. Y. Patil Medical College, Pune over a period of August 2006 to October 2008 among 30 cases as per the inclusion and exclusion criteria. All patients underwent arthroscopy, clinical examination and histopathology of knee joint tissues. Comparison was made between clinical diagnosis and histopathology as well as between arthroscopy findings and histopathology. Results: Pain and swelling of knee joint was reported by all patients. Anemia was seen in 70% of the cases. The accuracy of arthroscopic diagnosis was more than clinical diagnosis. Where clinical diagnosis failed to diagnose conditions like villonodular synovitis, pyogenic synovitis and gouty arthritis, the arthroscopic diagnosis was 100% accurate in the first two conditions and 66.7% accurate in the last condition. Where clinical diagnosis was accurate to 80-83% in cases of rheumatoid arthritis, septic arthritis and tubercular arthritis, the arthroscopic diagnosis was 100% accurate. Where in case of osteoarthritis, the clinical diagnosis could identify only 20% of the conditions, arthroscopic diagnosis was able to diagnose 40% of the actual cases. Conclusions: Arthroscopic diagnosis was more accurate as compared to clinical diagnosis and it was almost 100% in all cases of knee joint diseases except in two. Thus arthroscopic diagnosis can be relied upon and treatment can be started on this basis in view of time consuming and costly histopathological tests.